Etching of polymers, proteins and bacterial spores by atmospheric pressure DBD plasma in air. (27th February 2017) - Kuzminova, A; Kretková, T; Kylián, O; Hanuš, J; Khalakhan, I; Prukner, V; Doležalová, E; Šimek, M; Biederman, H
Abstract: Many studies proved that non-equilibrium discharges generated at atmospheric pressure are highly effective for the bio-decontamination of surfaces of various materials. One of the key processes that leads to a desired result is plasma etching and thus the evaluation of etching rates of organic materials is of high importance. However, the comparison of reported results is rather difficult if impossible as different authors use diverse sources of atmospheric plasma that are operated at significantly different operational parameters. Therefore, we report here on the systematic study of the etching of nine different common polymers that mimic the different structures of more complicated biological systems, bovine serum albumin (BSA) selected as the model protein and spores of Bacillus subtilis taken as a representative of highly resistant micro-organisms. The treatment of these materials was performed by means of atmospheric pressure dielectric barrier discharge (DBD) sustained in open air at constant conditions. All tested polymers, BSA and spores, were readily etched by DBD plasma. However, the measured etching rates were found to be dependent on the chemical structure of treated materials, namely on the presence of oxygen in the structure of polymers.